Flexible Flaps Inspired by Avian Feathers Can Enhance Aerodynamic Robustness in low Reynolds Number Airfoils - Murayama, Yuta; Nakata, Toshiyuki; Liu, Hao (Frontiers in Bioengineering and Biotechnology, 2021)
Unlike rigid rotors of drones, bird wings are composed of flexible feathers that can passively deform while achieving remarkable aerodynamic robustness in response to wind gusts. In this study, we conduct an experimental study on the effects of the flexible flaps inspired by the covert of bird wings on aerodynamic characteristics of fixed-wings in disturbances. Through force measurements and flow visualization in a low-speed wind tunnel, it is found that the flexible flaps can suppress the large-scale vortex shedding and hence reduce the fluctuations of aerodynamic forces in a disturbed flow behind an oscillating plate. Our results demonstrate that the stiffness of the flaps strongly affects the aerodynamic performance, and the force fluctuations are observed to be reduced when the deformation synchronizes with the strong vortex generation. The results point out that the simple attachment of the flexible flaps on the upper surface of the wing is an effective method, providing a novel biomimetic design to improve the aerodynamic robustness of small-scale drones with fixed-wings operating in unpredictable aerial environments.